Prophylactic Pancreatic Stents in High-Risk Population and Post-Endoscopic Retrograde Cholangiopancreatography Pancreatitis: - Zamani, Mohammad Mahdi; Ajdarkosh, Hossein; Hemasi, Gholamreza; Zamani, Farhad; Sohrabi, Masoudreza; Khoonsari, Mahmoodreza (Galen Medical Journal, 2015)
Background: Acute pancreatitis is a common complication of endoscopic retrograde cholangiopancreatography (ERCP). Several medical and surgical procedures have been analyzed in prevention of post-ERCP pancreatitis as a major post-ERCP complication, so we conducted a study to assess the role of prophylactic pancreatic stents on prevention and severity of post-ERCP pancreatitis. Materials and Methods: This case control studied adult patients undergoing ERCP at the ERCP unit of a referral educational hospital. Data of the case (stent, N=90) and control (non-stent) (N=105) groups were retrieved from medical records. In our center, sphinctrerotomy was performed for 103 patients of non-stent group and successful pancreatic stent placement was done in 86 patients of stent group in a standard fashion. In stent group, a 5F, 4 centimeter pancreatic stent was emplaced over a guide wire under fluoroscopic guidance. All post–ERCP pancreatitis and major complications of all patients were retrieved too. Results: Of 255 enrolled patients, 195 were at high risk of post-ERCP pancreatitis allocated in two groups of this study. Successful pancreatic stent placement was done in 86 patients (95.6%) of stent group. There was no major complication during procedures. The migration of pancreatic duct stent was diagnostic in 3 (3.5%) patients. The overall post ERCP pancreatitis was 4.0% and 16.6% in stent and non-stent groups, respectively. Conclusion: Based on our findings in this study, we strongly recommended pancreatic duct stent placement in high-risk patients; although the experience of endoscopist plays a crucial role. [GMJ.2015;4(2):67-71]